A HOLISTIC APPROACH TO THE WELL-BEING OF NURSES: A COMBINED EFFECTS APPROACH - Smith, Andrew (Advances in Social Sciences Research Journal, 2022)
Well-being at work is a major occupational health and safety issue for nurses. Past research shows that investigation of the well-being of nurses requires a multi-faceted approach which considers a range of predictors and outcomes. Research on topics such as stress and fatigue show that combining risk factors leads to the best predictor of these negative outcomes, and similar results have been found for positive outcomes. Organisational factors, rather than operational ones, have the greatest impact on well-being. Aim The present study compared the predictive power of the combined risk factors based on organisational and personal characteristics from the Well-being Process Questionnaire (WPQ) with the Expanded Nurses Stress Scale (ENSS) which covers a range of operational issues such as dealing with death and dying, interacting with relatives of patients and issues with senior members of staff, and with recent hassles (H) and the extent to which they were flourishing (F) Method A secondary analysis of data collected by Williams, Pendlebury and Smith (2017) was carried out. This study had a sample of 178 nurses who were given the WPQ, ENSS, and the H and F scales. The predictors of well-being (job demands, job resources, social support, coping styles and positive personality) were used to create a single score (negative predictors – positive predictors). The outcomes were also summed to create a single well-being score (negative outcomes-positive outcomes). The initial analysis examined the association between the combined predictors score, the ENSS score, the H and F scores and the well-being outcome. All of the variables were then included in a single regression analysis. Results Univariate analyses showed significant correlations between the independent variables and the well-being score. Regression analyses showed a significant effect of the combined predictors score on well-being. The ENSS score was no longer significant, but the H and F scores had additional significant effects on well-being. Conclusion The combined effects of established predictors of well-being were demonstrated in this study. Addition of the ENSS score had no significant effect, and the univariate association of it with well-being could be accounted for by the combined effects score. Hassles and flourishing scores did have a significant effect on well-being, even when combined effects were included in the model.